Analisis kesesuaian gambar ilustrasi dengan teks narasi pada buku bahasa indonesia lihatlah sekitar kelas 4 sd - Haq, Muhammad Hash Hashol; Sukarno, Sukarno; Wahyuningsih, Siti (Jurnal Pendidikan Dasar, 2023)
This study aims to analyze and describe the alignment between illustrative images and narrative text in the Indonesian language book "Lihatlah Sekita" from the grade 4 elementary school. This research is a type of document analysis with a qualitative descriptive approach. The research data consists of an analysis of the alignment of visual aspects in illustrative images with verbal aspects in narrative text based on Allan Paivio's dual coding theory. The data analysis technique used is the interactive description analysis model by Miles and Huberman. The results of this study show that there are high percentage of alignment between illustrative images and narrative text. The percentage of alignment between illustrative images and narrative text in the book is as follows: story 1 at 100%, story 2 at 94.12%, story 3 at 95%, story 4 at 100%, story 5 at 94.74%, story 6 at 100%, story 7 at 100%, story 8 at 100%, story 9 at 100%, story 10 at 87.5%, story 11 at 100%, story 12 at 100%, and story 13 at 100%. Essentially, the alignment between illustrative images and narrative text can influence students' comprehension of the narrative text content.